Application of an expert system shell in the preliminary design of offshore supply vessels - Mainal, Mohd. Ramzan (Penerbit UTM Press, 1993)
This paper presents the application of expert system programming in preliminary ship design with particular emphasis on offshore supply vessels. Instead of using one of the conventional programming expert system languages, the system is developed using an expert system shell, Leonardo. The design program is written in such a way that it is user friendly as well as giving the user full control over the progress of the design. The algorithms developed in this system are based on extensive research on existing offshore supply vessels.